Structural, Electronic, and Magnetic Properties of Sr\(_{1-x}\)Mn\(_{x}\)F\(_{2}\) Alloys Studied by First-principles Calculations - Do Minh, Hoat; Sanchez, Jonathan Guerrero; Perez, Rodrigo Ponce; Rivas Silva, Juan Francisco; Cocoletzi, Gregorio Hernandez (Communications in Physics, 2022)
In this work, the structural, electronic, and magnetic properties of the Sr\(_{1-x}\)Mn\(_{x}\)F\(_{2}\) (x = 0, 0.25, 0.5, 0.75, and 1) compounds are investigated using first-principles calculations. Crystallizing in fluorite structure, SrF\(_{2}\) is a magnetism-free indirect gap insulator with band gap of 11.61 eV as determined by the reliable mBJK functional. Mn substitution induces the magnetic insulator behavior as both spin configurations exhibit large band gaps with a strong spin-polarization. Specifically, spin-up energy gaps of 8.554, 7.605, 6.902, and 6.154 eV are obtained for Sr\(_{0.75}\)Mn\(_{0.25}\)F\(_{2}\), Sr\(_{0.5}\)Mn\(_{0.5}\)F\(_{2}\), Sr\(_{0.25}\)Mn\(_{0.75}\)F\(_{2}\), and MnF\(_{2}\), respectively. Whereas, the spin-down state shows larger values of 8.569, 8.864, 9.307, and 9.837 eV, respectively. Consequently, significant magnetization is induced and an integer total spin magnetic moment of 5 \(μ_{B}\) is obtained, being produced mainly by the spin-up Mn-3d state. Finally, the formation enthalpy and cohesive energy are determined, which indicate good thermodynamic and structural stability of the studied materials. Results suggest that Mn substitution at the Sr-sites of SrF\(_{2}\) compound may be an efficient approach to create new magnetic materials to be used in the spintronic devices.